The Efffects of the Drawing-series Instructional Package on Nigeria Junior Secondary Schools Art - Odewumi, Michael Olubunmi (Indonesian Journal of Curriculum and Educational Technology Studies, 2020)
The tedious condition of Arts Students in Nigerian Junior Secondary School has been attributed to the inadequate text and soaring cost of existing ones. Therefore, it is important for instructors to adapt their teaching tools. This study used a quasi-experimental to determine the effect of using Drawing-series Instructional Package by comparing the pre and post-test results using Drawing-series Instructional Package (DIP) and Test Instrument of Drawing-series (TID). Ninety students were involved as samples of this research in two groups of the experimental class and the control class. The result showed that there was no significant difference in students’ performance based on DIP and student gender had no effect on student performance. According to the finding of this research DIP is recommended to be developed and used in teaching handicraft subjects in Nigerian schools. Abstrak Kondisi menjemukan siswa-siswi di Sekolah Menengah Pertama (SMP) telah diasosiasikan dengan kelangkaan teks dan biaya pembelajaran yang mahal. Oleh karena itu, penting bagi guru untuk mengadaptasi perangkat-perangkat pengajarannya. Penelitian ini menggunakan eksperimen semu untuk mengetahui efek penggunaan Drawing-series Instructional Package dengan membandingkan pra dan post-test menggunakan Drawing-series Instructional Package (DIP) dan Test Instrument of Drawing-series (TID). Hasil penelitian ini menunjukkan bahwa tidak ada perbedaan signifikan dalam capaian belajar siswa mengacu pada DIP dan kategori gender siswa tidak juga memengaruhi kinerja atau capaian belajar siswa. Berdasarkan temuan penelitian ini, DIP disarankan untuk dikembangkan dan digunakan dalam pembelajaran mata pelajaran kriya di sekolah-sekolah di Nigeria.